2018
DOI: 10.1115/1.4039959
|View full text |Cite
|
Sign up to set email alerts
|

Thermohydrodynamic Analysis of High-Speed Water-Lubricated Spiral Groove Thrust Bearing Using Cavitating Flow Model

Abstract: A thermohydrodynamic lubrication model of turbulent cavitating flow for high-speed spiral groove thrust bearing was developed considering the effects of cavitation, turbulence, inertia, breakage, and coalescence of bubbles. Comparing with the classical thermohydrodynamic model, this model can predict not only the distributions of pressure and temperature rise but also the distribution of bubble volume and bubble number density. Static characteristics of the water-lubricated spiral groove thrust bearing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“… trueF denotes the external body forces and τ= is the stress tensor. The stress tensor can be evaluated by Lin et al (2018b): where μ is the fluid viscosity, and I represents the unit tensor.…”
Section: Theory and Methodsmentioning
confidence: 99%
“… trueF denotes the external body forces and τ= is the stress tensor. The stress tensor can be evaluated by Lin et al (2018b): where μ is the fluid viscosity, and I represents the unit tensor.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…They observed that the application of a spiral grooved face seal reduces the value of friction coefficient up to 10 times lower as compared to the non-grooved face seal. Lin et al 36 investigated the high-speed spiral grooved thrust pad bearings under thermo-hydrodynamic lubrication mode considering the cavitation effect and they found that the maximum temperature rise of the bearing is reduced due to the cavitation effect. Li et al 37 performed several experiments to investigate the reverse spiral groove seal's cavitation characteristics using the upstream pumping function.…”
Section: Spiral Groove Thrust Pad Bearingmentioning
confidence: 99%
“…Yu Chen et al 30 conducted a numerical investigation by implementing user‐defined computational fluid dynamics code on hydrodynamic journal bearing to study the influence of thermal and cavitation phenomenon and reported that for extreme operating condition groove shape is ideal. Lin et al 31,32 conducted a theoretical investigation on high speed water lubricated groove to study the influence of thermal and cavitation phenomenon and reported that cavity and inertia have significant effects on journal bearing. Alireza Solghar 33 conducted a numerical investigation on user‐defined computational fluid dynamics code on hydrodynamic journal bearing by implementing the lattice Boltzmann method to study the bearing performance characteristics and reported that ellipticity ratio has profound effects on the bearing load capacity, oil flow rate, and bearing power loss.…”
Section: Introductionmentioning
confidence: 99%